MRPC3b mass production for CBM-TOF and eTOF at STAR - Hu, Dongdong; Sauter, Dennis; Wang, X.; Sun, Y.; Deppner, Ingo Martin; Herrmann, Norbert; Simon, Christian; Weidenkaff, Philipp; Brandt, Jonathan; Zhou, J.; Shao, M.; Li, C.; et al. (Journal of Instrumentation, 2019)
The Compressed Baryonic Matter (CBM) spectrometer aims to study strongly interacting matter under extreme conditions. The key element providing hadron identification at incident energies between 2 and 11AGeV in heavy-ion collisions at the SIS100 accelerator is a Time-of-Flight (TOF) wall covering the polar angular range from 2.5̂-25̂ and full azimuth. CBM is expected to be operational in the year 2024 at the Facility for Anti-proton and Ion Research (FAIR) in Darmstadt, Germany. The existing conceptual design foresees a 120 m2 TOF-wall composed of Multi-gap Resistive Plate Chambers (MRPC) which is subdivided into a high rate region, a middle rate region and a low rate region. The MRPC3b Multistrip-MRPCs, foreseen to be integrated in the low rate region, have to cope with charged particle fluxes up to 1 kHz/cm2 and therefore will be constructed with thin float glass (0.28 mm thickness) as resistive electrode material. In the scope of the FAIR phase 0 program it is planned to install about 36% of the MRPC3b counters in the east endcap region of the STAR experiment at BNL as an upgrade for the Beam Energy Scan campaign (BESII) in 2019/2020.
Published 11 June 2019
Gesehen am 19.02.2020